The possible role of cytomegalovirus infection and pro-inflammatory IL_2 cytokine in preeclampsia - Al Barzangy, Razao Kamal; Salh, Khonaw Kader; Hamasaeed, Payman A.; Hussain, Saeed Khulam (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objective: Fragmentary evidence suggests that trophoblast viral infection may play a role in placental dysfunction leading to complications like Preeclampsia. Among these, placental exposure to CMV induces an inflammatory response that precedes invasive trophoblast cell death. This study aimed to assess the frequency of anti-CMV IgG seropositivity and IL2 level in serum in patients with preeclampsia compared to normotensive control pregnant women. Methods: A total of 90 women were enrolled, of which 60 had preeclampsia and 30 normotensive pregnant women as the control. A serum sample was collected from each subject and was investigated for anti-CMV IgG serostatus and IL-2 concentration using Enzyme-Linked Immunosorbent Assay (ELISA) based kits. Results: In preeclamptic and normotensive pregnant women, 33.3% and 16.6% of the tested sera were seropositive for anti CMV IgG antibodies respectively (P = 0.136). Early onset preeclamptic women revealed a high frequency of anti-CMV seropositivity (80%) when compared with late onset Preeclampsia (20%). Cytokine assessment revealed a higher IL-2 level in preeclamptic women seropositive for anti-CMV IgG although statistically was not significant (P = 0.14), but in normotensive women, the IL-2 level was significantly higher in sera seropositive for anti-CMV IgG (P = 0.02). Conclusion: This study delineates a high frequency of anti-CMV IgG antibodies particularly those with early onset preeclampsia; with no significant difference for the IL-2 level.